Obraz rzeczy – słowo – słowo Innego - Tabakowska, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The author attempts to determine the role of imagination in (literary) translation Definitions of various types of imagination, taken from dictionary, or discussed in psychological works, are referred to in relation to processes occurring in the mind of a recipient of text (the readertranslator and the intended reader of translation) confronted with the original, defined as “the Other’s word.” The discussion is illustrated by three selected examples of relations between imagination and foreign cultural determinants: a poet’s reference to an outdated, idealised cognitive model, reference to the Other’s realities of material culture, and grammatical determination of a cultural cognitive model. The article ends with conclusions related to the notion of translation equivalence.